As terceiras margens: um estudo da rememoração em primeiras estórias de João Guimarães Rosa - Pimentel, Luanda Moraes (2014)
The proposal of this dissertation is to study the reminiscence in (1962) João Guimarães Rosa’s Primeiras estórias, having as theoretical support Plato's Theory of Recollection. For the philosopher, the soul is immortal and will be continuously reborn in different bodies. Furthermore, when a person learns something, a recollection occurs, because he simply regains memory of knowledge already acquired by his soul in the world of ideas. The intention, based on this Plato's theory, is to understand the mysterious events in Rosa's stories by distancing oneself from traditional logic when it comes to the enigmatic behavior of the characters. Because the Primeiras estórias book consists of many narratives, the corpus was restricted to seven short stories: “A terceira margem do rio”, “A menina de lá”, “Sorôco, sua mãe, sua filha”, “Nenhum, nenhuma”, “Um moço muito branco”, “As margens da alegria” e “Os cimos”.